Treatment in the home setting with intermittent pneumatic compression for a woman with chronic leg ulcers: a case report - Katrina Young; Harrison Ng Chok; Lesley Wilkes (BMC, 2017)
Abstract Background Intermittent Pneumatic Compression (IPC) is shown to improve the healing rate of Venous Leg Ulcers (VLU) in the hospital setting. The current Australian "Gold Standard" treatment according to the Australian and New Zealand Wound Management Associations' (AWMA) Prevention & Management of Venous Leg Ulcer guidelines is compression, generally in the form of bandaging then progressing to hosiery once wounds are healed to prevent recurrence. This is recommended in conjunction with other standards of wound management including; nutrition, exercise, client education and addressing underlying pathophysiology and psychosocial factors. Compression bandaging is predominantly attended by community nurses in the clients' home. Barriers to delivery of this treatment include; client concordance and or suitability for bandaging including client habitus, (shape of legs), client lifestyle, clinician knowledge and clinicians physical ability to attend bandaging, in particular for obese clients with limited mobility who pose a manual handling risk to the clinician themselves. The use of IPC may assist in mitigating some of these concerns, therefore it would seem wise to explore the use of IPC within the home setting. Case presentation This paper will present an original case report on the successful treatment of a woman living with chronic bilateral lower leg ulcers using IPC as an adjunct treatment in her home. This paper supports recommendations to explore the use of IPC therapy in the home setting, for treatment of chronic leg ulcers requiring compression. Conclusion Use of IPC in the home is anticipated to improve client involvement, concordance, client outcomes and reduce risk to staff applying conventional compression bandaging systems, particularly for obese clients with limited mobility.